Cevaplar

2012-11-27T17:02:17+02:00

1) x^3 + 5x^2 - 4x - 20 = 0

2) (x^3 + 5x^2) - (4x + 20) = 0

3)  x^2(x + 5) -4(x + 5)

4) (x+5)(x^2 - 4)

5) (x+5)(x-2)(x+2)

köklerden biri 2 olduğuna göre x+5=0 , x=-5  ve x+2=0 ,x=-2 ve x-2=0, x=2

ç={-5,-2,2} , a^2+b^= (-5^2)+(-2^2) =25+4=29 

0
  • Eodev Kullanıcısı
2012-11-27T17:20:01+02:00

1) x^3 + 5x^2 - 4x - 20 = 0

2) (x^3 + 5x^2) - (4x + 20) = 0

3)  x^2(x + 5) -4(x + 5)

4) (x+5)(x^2 - 4)

5) (x+5)(x-2)(x+2)

köklerden biri 2 olduğuna göre x+5=0 , x=-5  ve x+2=0 ,x=-2 ve x-2=0, x=2

ç={-5,-2,2} , a^2+b^= (-5^2)+(-2^2) =25+4=29 

YANİ ARKADAŞIN DEDİĞİ DOĞRU

0